Dimeric and trimeric catenation of giant chiral (8 + 12) imine cubes driven by weak supramolecular interactions - Benke, Bahiru P.; Kirschbaum, Tobias; Graf, Jürgen; Gross, Jürgen H.; Mastalerz, Michael (Nature chemistry, 2022)
Mechanically interlocked structures, such as catenanes and rotaxanes, are fascinating synthetic targets and some are used for molecular switches and machines. Today, the vast majority of catenated structures are built upon macrocycles and only a very few examples of three-dimensional shape-persistent organic cages forming such structures have been reported. However, the catenation in all these cases was based on a thermodynamically favoured π-π-stacking under certain reaction conditions. Here, we show that catenane formation can be induced by adding methoxy or thiomethyl groups to one of the precursors during the synthesis of chiral [8 + 12] imine cubes, giving dimeric and trimeric catenated organic cages. To elucidate the underlying driving forces, we reacted 11 differently 1,4-disubstituted terephthaldehydes with a chiral triamino tribenzotriquinacene under various conditions to study whether monomeric cages or catenated cage dimers are the preferred products. We find that catenation is mainly directed by weak interactions derived from the substituents rather than by π-stacking.
Im Titel steht der Ausdruck "8 + 12" in eckiger Klammer
Gesehen am 11.01.2023